Effects of anion and alkyl chain length of cation on the thermophysical properties of imidazolium-based ionic liquid. (2021) - Anggraini, Y; Sutjahja, IM; Kurnia, D; Viridi, S
Abstract: This study focused on the effects of anions and the alkyl chain length of cations on the thermophysical properties of imidazolium-based ionic liquid (ILs). The data were obtained from references and the NIST database. The studied parameters include the melting temperature ( Tm ), glass transition temperature ( Tg ), decomposition temperature ( Td ), enthalpy of fusion (Δ Hm ), and thermal conductivity ( λ ). The variations of Tm with the anions in [C16 MIM][A] where A = Br, Cl, BF4, PF6, and TFO, generally decreased with increasing anion radius, except for A = PF6, due to strong hydrogen bonds for the sake of an F atom. The values of the critical temperatures ( Tm, Tg, and Td ) generally show a strong variation with the number of carbon atom or alkyl chain length (the number of n in [C n MIM][A] for A = BF4, NTf2, and PF6 ). The variation of Tm corresponding to n shows non-monotonous variations. This characteristic is the result of the combination of interaction potentials in the crystalline and liquid phases. The variation of Tg corresponding to n shows even–odd alternation, presumably due to the competition between the electrostatic and van der Waals forces. Many types of ILs have a relatively high Td value, enabling them to remain in the liquid state above 400 °C, they have excellent catalytic activity and dynamic properties. The variation of Td with n appears different to that of Tm . Furthermore, the variation of Δ Hm with n seems to follow that of Tm . This behaviour is in accordance with the thermodynamic relation between Δ Hm, Tm, and the entropy of the system. The values of λ varied weakly with the alkyl chain length, and strongly depend on the type of anion.